Pancreatitis with pancytopenia: are we missing a common diagnosis? - V., Sandhya; M., Alok; R., Madhusudhan M. (International Journal of Research in Medical Sciences, 2023)
Acute pancreatitis with pancytopenia is a rare unreported complication of dengue non-hemorrhagic fever. A 16-year-old girl came to the emergency with complaints of loose stools and vomiting with pain abdomen and mild fever the previous day. She was diagnosed to have acute pancreatitis, which evolved into pancytopenia. She was then diagnosed with dengue fever. She was successfully managed conservatively nil orally, with intravenous fluids therapy as per the dengue protocol, timely investigations and watchful management. Acute pancreatitis with pancytopenic blood picture must point the clinician to underlying causes like dengue in endemic areas.